Greeks bearing gifts [large type] - Kerr, Philip (Kerr, Philip. Bernie Gunther novel., 2018)
Knowing New York Times best selling author Philip Kerr's delight in subterfuge and obfuscation, listeners can rest assure that nothing is what it seems when Bernie Gunther discovers war criminals living freely in Europe.